2021
DOI: 10.1098/rsta.2020.0436
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack growth in epoxy polymer nanocomposites

Abstract: The present paper describes detailed analyses of experimental data for the cyclic-fatigue behaviour of epoxy nanocomposite polymers. It has been shown that the data may be interpreted using the Hartman–Schijve relationship to yield a unique, ‘master’, linear relationship for each epoxy nanocomposite polymer. By fitting the experimental data to the Hartman–Schijve relationship, two key materials parameters may be deduced: (i) the term A , which may be thought of as the fatigue equivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Notwithstanding this intriguing finding, that the da/dN versus Δκ master-relationships obtained for the 'FM94' adhesive, the 'FM73' adhesive and the automotive adhesive are all very similar, it should be noted that previous work [15] has shown that when a far wider range of formulations of toughened epoxy polymers is studied the overall picture is more complex, i.e. not all adhesives have similar Hartman-Schijve master-relationships.…”
Section: The Hartman-schijve Approachmentioning
confidence: 83%
See 2 more Smart Citations
“…Notwithstanding this intriguing finding, that the da/dN versus Δκ master-relationships obtained for the 'FM94' adhesive, the 'FM73' adhesive and the automotive adhesive are all very similar, it should be noted that previous work [15] has shown that when a far wider range of formulations of toughened epoxy polymers is studied the overall picture is more complex, i.e. not all adhesives have similar Hartman-Schijve master-relationships.…”
Section: The Hartman-schijve Approachmentioning
confidence: 83%
“…This solution revealed that the near-tip stress field for rectilinearly orthotropic composites was indeed uniquely described by √𝐺𝐺. Thus, as explained in [9][10][11][12][13][14][15], the logical and corresponding extension of the Paris crack growth equation to FCG in adhesives, composites or nanocomposites, is to express da/dN as a function of ∆√𝐺𝐺, or of �𝐺𝐺 𝑚𝑚𝑚𝑚𝑚𝑚 ; and not of ∆𝐺𝐺, nor of 𝐺𝐺 𝑚𝑚𝑚𝑚𝑚𝑚 . An additional reason for using the square root of the energy release rate is that general graphical description of the data between using ∆√𝐺𝐺 and ∆𝐾𝐾 is homomorphic.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, variants of this approach have also been shown to be able to model delamination growth in composites as well as cohesive crack growth in adhesives and nanocomposites, see [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Glassy thermoset polymers have been demonstrated as highly useful materials, especially in structural, adhesive, and coatings applications, due to their robust mechanical properties, dimensional stability, and corrosion resistance. Their ability to serve as matrices for multifunctional composites also expands their design space into an even greater diversity of applications; however, the high cross-linking density, which can impart strength, typically inflicts the materials with brittleness and decreased toughness and prevents them from being effectively reprocessed or recycled. ,,, Some of this loss in toughness can be mitigated through extrinsic toughening mechanisms like the addition of core–shell rubber particles, copolymerization with thermoplastics, , or nano-/micro-scale structural heterogeneity, but, ideally, a neat, homogeneous thermoset matrix can be engineered to maintain its desirable properties without significant loss of toughness or reprocessability.…”
Section: Introductionmentioning
confidence: 99%